Pengaruh Person Organization Fit dan Person Job Fit Terhadap Kinerja Karyawan Pada Kopontren MBS Water Suci Manyar Gresik - Mohammad Fa'iqur Rifqi; Lilis Sugi Rahayu Ningsih (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This study aims to determine the effect of Person Organization Fit and Person Job Fit on Employee Performance in the Kopontren MBS Water Suci Gresik. This type of research used in this research is quantitative with associative analysis. The sampling technique used was a simple random sampling technique with a sample size of 40 Kopontren MBS Water Suci Gresik employees. This study uses data collection techniques using questionnaires, interviews, documentation and observation. In analyzing data using statistical methods using validity and reliability, classic assumption tests, and hypothesis testing with multiple linear regression formula. The results showed that, (1) Person Organization Fit Influenced Employee Performance in the Kopontren MBS Water. (2) Person Job Fit has a Significant Effect on Employee Performance in MBS Water Co-Controllers. (3) Person Organization Fit and Person Job Fit Have Simultaneous Effect on Employee Performance in the Kopontren MBS Water. Keywords: Person Organization Fit; Person Job Fit; Employee Performance